On the crystallization of austenitic carbide eutectic of chromium cast iron - E. I. Marukovich; V. Yu. Stetsenko; A. V. Stetsenko (Литьë и металлургия)
Crystallization of austenitic carbide eutectic of chromium cast iron is a nanostructural process in which iron, graphite and chromium nanocrystals play a major role. Austenite dendritic microcrystals are not solid solutions of carbon and chromium atoms in the γ-Fe crystal lattice. During the crystallization of chromium cast iron, oxygen and hydrogen atoms in their melts are demodifying elements that reduce the dispersion of microcrystals of eutectic austenite and carbide. Molecular hydrogen released on dendritic microcrystals of eutectic austenite and carbide prevents the branching of dendrites. This leads to demodification of the austenitic-carbide eutectic structure of chromium cast irons. Modifying elements of chromium cast iron reduce the concentrations of oxygen and hydrogen atoms in their melts. This increases the dispersion and branching of dendritic microcrystals of eutectic austenite and carbide during solidification of chromium cast iron. Nonmetallic inclusions of modifying elements (Mg, Ca, Ce, La) of chromium cast irons cannot be centers of crystallization of microcrystals of eutectic austenite and carbide. These crystallization centers are nanostructured formations of austenite and carbide.